THE DEVELOPMENT OF INTERACTIVE MULTIMEDIA WRITING EXPOSITIONAL TEXT BY IMPLEMENTING PROJECT BASED LEARNING IN STUDENT OF MTSN 1 MEDAN - Garin Akbar Aulia; Syahnan Daulay; Malan Lubis (Sensei International Journal of Education and Linguistic, 2021)
This study aims to determine the result of the development of interactive multimedia writing expositional text in Students MTsN 1 Medan. The media being developed is in the form of interactive multimedia. This type of research is development research based on the 4-D development model. The trial subjects consisting of design experts, material experts, Indonesian language teachers, and class VIII students of MTsN 1 Medan. The results showed that (1) the validation of the material experts included the eligibility of the content of 88.0% in the good category, the feasibility of the presentation of the learning module in 93.7% of the very good category, 95.8% of the interactive multimedia aspects of the very good category, 92 aspects of language assessment, 5% very good category, and project based learning aspects 83.3% good category (2) design expert validation includes initial design 89.2% with good category, content design 83.9% good category, media typography 83.3 good category, and illustration 87.5% good category. (3) the limited trial obtained a score of 82.79% with good criteria (4) The extended trial obtained a score of 80.04% in good category. Results of learning to produce a text exposition s Before the use of interactive multimedia to the model of project-based learning at 62 , 9 while the learning outcomes produced expositional texts using interactive multimedia with project based learning models gained 80.8. The difference obtained was 18 from before and after using digital media with the application of project based learning . This study have the implication that media is being developed will practically contribute especially in the implementation of the learning process for teachers as supplementary teaching materials to ease the burden on the material being taught to be independent and classical. Furthermore, students can improve the quality of learning, especially in expositional writing text activities with the content of learning interactive multimedia in it with project based learning model . Related to activities of working together and motivating each other to complete an expositional text.